PTU-250 Management of anticoagulant and antiplatelet therapy in patients undergoing endoscopic procedures: compliance with existing guidelines. (28th May 2012) - Patani, O; Khalid, S
Abstract : Introduction: It is not uncommon for patients on anticoagulants and antiplatelets to undergo endoscopic procedures. The main issue in such cases is balancing the risk of gastro-intestinal bleed and the need for anticoagulation. Recognising this, the British Society of Gastroenterology (BSG) issued in 2008 practice guidelines on the management of anticoagulants and antiplatelet therapy in patients undergoing endoscopic procedures. Aspirin, Clopidogrel and Warfarin are the most commonly used antiplatelets and anticoagulants in the UK. Aspirin is recommended to be continued for all endoscopic procedures while Clopidogrel and Warfarin should be tailored to the bleeding risk category of the procedure and the thrombotic risk of the patient's condition. Our clinical practice was retrospectively audited to assess adherence to the BSG guidelines. Methods: All patients on antiplatelets and anticoagulants undergoing endoscopic procedures except ERCP were included in the audit. Data were collected from case notes, endoscopy records and the Éclair pathology reporting system. Results: 48 patients were identified to have 52 procedures with 37 (64%) on Aspirin alone, 6 (10%) on Clopidogrel alone, 9 (16%) on Warfarin alone, 4 (7%) on Aspirin and Clopidogrel and 2 (3%) on Aspirin and Warfarin. 16/37 (43%) in Aspirin alone group had it stopped inappropriately for 3–7 days. 3/6 (50%) Clopidogrel alone patients had it stopped while having one high risk procedure and two low risk procedures. Warfarin was stopped inappropriately in 7/9 (78%) patients undergoing eight procedures. Conclusion: Endoscopic procedures have evolved over the years to include increasingly complex and invasive procedures carrying risk of serious complications including bleeding. Also significant proportions of patients are on multiple medications including anticoagulants and antiplatelets. It is therefore essential that appropriate management plan for the anticoagulant and antiplatelet therapy should be made to minimise the haemorrhagic and thromboembolic risk when requesting endoscopic procedures. The findings of this audit underline significant non-compliance to existing guidelines with potential serious implications for the standard of patient care. While endoscopy is performed by trained endoscopists, the procedures are requested by clinicians with variable knowledge and awareness of the existing BSG guidelines. This hurdle can be overcome using a combination of raising awareness through educational events and modification of the endoscopy requesting software by including a link to the anticoagulation management guideline flow chart making it accessible to the clinicians at the time of requesting. We hope these measures will result in improvement of service and make endoscopy safer in our hospital. Competing interests: None declared.